Improvement of composition of TC4 alloy for medical implant and its supporting post-processing
By adding trace strontium elements to TC4 titanium alloy, the degradable organic strontium compound is formed, which solves the problem of insufficient biological activity of titanium alloy implants, improves bone binding force and implant survival time, and reduces the failure rate.
Patent Information
- Application Number
- CN202411846665.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
AI Technical Summary
The lack of biological activity of titanium alloy implants in the human body leads to unqualified firm bonding or fixation with bones, which leads to implant failure and high failure rates.
By adding trace rare earth element strontium to TC4 titanium alloy, degradable organic strontium compounds are formed, which promotes the climbing and growth of human tissues and rapid repair of bone tissues, and increases bone integration biological activity.
The biological activity of titanium alloy implants and bones is enhanced, the binding force between implants and bones is reduced, the implant failure rate is reduced, and the survival time of the implant is extended by the continuous trace release of organic strontium compounds.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy material preparation, and in particular to improvement of the composition of medical implantable TC4 alloy and its supporting post-processing. Background Art
[0002] Titanium alloys have attracted widespread attention in the biomedical field due to their excellent properties: corrosion resistance, low elastic modulus and excellent biocompatibility. Usually, the medical field directly uses the naturally formed oxide layer on the surface of titanium alloys to promote bone integration, relying on the low elastic modulus of titanium alloys such as TC4 to reduce bone stress shielding. However, despite this, the bone integration bioactivity of titanium alloys such as TC4 is still not enough to achieve physiological adhesion between implants and bones, resulting in unstable mechanical properties and high implant failure rate.
[0003] So far, most of the research work on enhancing the bioactivity of titanium alloys such as TC4 has focused on improving the bone-implant interface. Enhance interface integration through physical or chemical methods. Physical methods focus on using mechanical methods (plasma coating, sandblasting, anodizing, machining and acid etching, etc.) to adjust the surface roughness and morphology of TC4 and other titanium alloy printed implants, improve surface roughness, thereby optimizing the level of surface energy, promoting matrix protein adsorption, bone riveting, and ultimately improving the level of bone integration.
[0004] The chemical method is to add a coating to the implant surface through physical chemistry, biochemistry and other technologies to provide a bioactive implant surface. Usually, organic molecules such as growth factors and peptide bonds are coated on the implant surface to anchor specific cells and promote cell growth response.
[0005] Titanium alloy is a commonly used implant in the field of orthopedics. Although it is widely used as an orthopedic implant due to its high strength, rigidity and fracture toughness, the serious defect of titanium alloy implants is that they cannot be integrated into the body environment on a large scale, and thus cannot achieve long-term survival, resulting in implant failure. Solving such problems requires another repair surgery, and the risks, costs and complications of the repair surgery are higher than those of the first round of implantation. Usually, an important factor in the failure of titanium alloy implants is aseptic loosening, which is caused by the poor adhesion or fixation of titanium alloy implants to bones, thus failing to achieve optimal functionality and durability.
[0006] Therefore, the improvement of the composition of the medical implantable TC4 alloy and the supporting post-processing provided by the present invention are intended to improve the biological activity between the titanium alloy implant and the human skeleton, and optimize the interaction and combination between the titanium alloy implant and the human skeleton. By adding a trace amount of rare earth element strontium to TC4, under the condition of ensuring personal safety, the molecules of the trace strontium element are released to form a degradable organic strontium compound that is released on the surface of the TC4 titanium alloy implant, promoting the attachment and growth of human tissue, improving the rapid repair of bone tissue, and increasing the biological activity of bone integration. Summary of the invention
[0007] The purpose of the present invention is to provide an improved composition of medical implantable TC4 alloy and supporting post-processing. By adding a trace amount of rare earth element strontium to TC4, under the condition of ensuring personal safety, the trace amount of strontium molecules are released to form a degradable organic strontium compound that is released on the surface of the TC4 titanium alloy implant, thereby promoting the attachment and growth of human tissue, improving the rapid repair of bone tissue, and increasing the biological activity of bone integration.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A medical implantable TC4 alloy, which includes, by mass percentage, Al (aluminum) 5.5-6.75wt%, V (vanadium) 3.5-4.5wt%, Fe (iron) ≤0.3wt%, C (carbon) ≤0.08wt%, O (oxygen) ≤0.20wt%, N (nitrogen) ≤0.05wt%, H (hydrogen) ≤0.015wt%, Sr (strontium) 0.02-0.08wt%, and the remainder Ti (titanium) and unavoidable impurities.
[0010] The present application also claims a post-processing process for a medical implantable TC4 alloy product, using the above-mentioned medical implantable TC4 alloy, comprising the following steps:
[0011] (1) adding raw materials according to the composition and proportion of the above-mentioned medical implantable TC4 alloy, the raw material alloy is smelted at least twice, and then subjected to ingot casting, drawing, shaping, and rounding processes to produce a master alloy rod;
[0012] (2) The master alloy rod is loaded onto the EIGA device, and the master alloy rod is quickly melted to form powder;
[0013] (3) screening the powder to obtain powder of a specified particle size, and printing the powder on the powder;
[0014] (4) After the printing of the workpiece is completed, a stress removal heat treatment is performed, and a surface roughness treatment process is performed on the surface. After reaching the specified surface roughness, the workpiece is soaked in erythritol solution, and then subjected to conventional heat treatment. After the workpiece returns to room temperature, it is soaked in erythritol solution again, so that its surface is fully in contact with the strontium ions generated in situ after the heat treatment, and a trace strontium compound that can continuously release a trace amount of alternative growth factors is formed on the surface;
[0015] (5) Subsequently, routine operations can be performed according to surgical requirements.
[0016] Preferably, in step (1), the first smelting of the at least two smeltings is carried out by a consumable electrode, a non-consumable electrode, an electron beam cooling hearth or a plasma arc cooling hearth furnace.
[0017] Preferably, in step (1), the second melting of the at least two meltings or the multiple meltings after the second melting are all vacuum melted in vacuum arc remelting, and alloy additives are not allowed to be added in the last vacuum melting.
[0018] Preferably, in step (3), the printing powder particle size D10 of the printed part is set to be above 18 microns, and the powder particle size D90 is set to be below 65 microns.
[0019] Preferably, in step (3), the print layer thickness of the printed part is 0.03-0.06 mm, the scanning interval is 0.12-0.18 mm, the scanning power is 280-300 W, and the main body scanning rate is 1300-1600 mm / s; high-speed printing avoids rare earth element burning.
[0020] In the above technical solution, the master alloy rod is loaded onto the EIGA device, and a faster rod feeding speed and a larger power are specified to quickly melt the rod to avoid burning and segregation of rare earth elements.
[0021] Working mechanism of the present invention:
[0022] By adding a trace amount of rare earth element strontium to TC4, under the condition of ensuring personal safety, through the release of trace strontium molecules, a degradable organic strontium compound is formed and released on the surface of TC4 titanium alloy implants, promoting the growth of human tissue, improving the rapid repair of bone tissue, and increasing the biological activity of bone integration. Strontium and calcium, the main element of human bones, belong to the same family in the periodic table, and have the function of inhibiting osteoclast absorption and improving osteogenic activity. In the early stage, strict control of the composition of strontium added to TC4 was carried out, so that it could be stably released in trace amounts within a certain period of time, effectively replacing the existing means of coating growth factors on the surface of titanium alloy bone implants, avoiding the shortcomings of high cost, short survival time, and short action time of growth factors. This method can release organic strontium elements generated in situ by itself, which is low-cost and long-lasting compared to the later coating of growth factors. In addition, it can further reduce bone stress shielding and further improve the success rate of surgery. Before implantation, the titanium alloy implant needs to be post-treated by immersing it in erythritol solution so that the erythritol solution forms a uniform coating on the surface to further promote cell adhesion.
[0023] Due to the application of the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0024] 1. The present invention adds a trace amount of rare earth element strontium to TC4. Under the condition of ensuring personal safety, the trace amount of strontium molecules are released to form a degradable organic strontium compound, which is released on the surface of the TC4 titanium alloy implant to promote the attachment and growth of human tissue, improve the rapid repair of bone tissue, and increase the biological activity of bone integration;
[0025] 2. The titanium alloy-strontium element effect of the erythritol liquid coated in the present invention is significantly improved. The erythritol liquid can chelate with the metal through its covalent bond to form an adherent film on the metal substrate, and it can remain in the human body for a long time. The slow release also helps the tissue and the implant to be well combined;
[0026] 3. The post-processing operation of the present invention is simple and inexpensive. The biodegradable organic strontium compound released in trace amounts continuously has a longer action time than the survival time of growth factors, which is more conducive to improving the success rate of surgery. DETAILED DESCRIPTION
[0027] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.
[0028] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0029] Example 1
[0030] The present embodiment provides a medical implantable TC4 alloy, wherein the TC4 titanium alloy comprises, by mass percentage: Al (aluminum) 6.11wt%, V (vanadium) 4.09wt%, Fe (iron) 0.145wt%, C (carbon) 0.006wt%, O (oxygen) 0.100wt%, N (nitrogen) 0.004wt%, H (hydrogen) 0.0006wt%, Sr (strontium) 0.07wt%, and the remainder Ti (titanium) and unavoidable impurities;
[0031] A post-processing process of a medical implantable TC4 alloy product, using the above-mentioned medical implantable TC4 alloy, comprises the following steps:
[0032] (1) adding raw materials according to the composition and proportion of the above-mentioned medical implantable TC4 alloy, the raw material alloy is subjected to two smelting processes, and then subjected to ingot casting, drawing, shaping, and rounding processes to produce a master alloy rod; wherein the first smelting is performed by a consumable electrode, a non-consumable electrode, an electron beam cooling bed, or a plasma arc cooling bed furnace, preferably a plasma arc cooling bed furnace; then the second smelting is performed by vacuum melting in a vacuum arc remelting process; the alloy additives are added during the first smelting;
[0033] (2) The master alloy rod is loaded onto the EIGA device, and the master alloy rod is quickly melted at a faster rod feeding speed and a higher power to form powder;
[0034] (3) Screening the powder to obtain a powder of a specified particle size, and printing the powder on the powder; since a trace amount of strontium is added to the powder, the application is that the printing powder particle size D10 is set to be above 18 microns, and the powder particle size D90 is set to be below 65 microns; the printing layer thickness is 0.04 mm, the scanning interval is 0.15 mm, the scanning power is 300 W, and the main scanning rate is 1500 mm / s;
[0035] (4) After the printing of the workpiece is completed, a stress removal heat treatment is performed, and a surface roughness treatment process is performed on the surface. After reaching the specified surface roughness, the workpiece is soaked in erythritol solution, and then subjected to conventional heat treatment. After the workpiece returns to room temperature, it is soaked in erythritol solution again to form a trace strontium compound on the surface that can continuously release a trace amount of alternative growth factors;
[0036] (5) Subsequently, routine operations can be performed according to surgical requirements.
[0037] Comparative Example 1
[0038] The titanium alloy composition of this comparative example is the same as that of Example 1, but it is conventional physical adsorption (simple coating).
[0039] Comparative Example 2
[0040] This comparative example is a conventional titanium alloy composition and conventional physical adsorption (simple coating).
[0041] The above embodiments and comparative examples were tested, and the test results are shown in Table 1.
[0042] Table 1
[0043] Test items Combination efficiency Cytotoxicity Delayed release factor Active form Example 1 57% 0.851 3% after one month Immobilization Comparative Example 1 60% 0.677 5% after one month Immobilization Comparative Example 2 86% 0.712 30% after one month Solubility
[0044] It can be seen from Table 1 that the conventional method has the highest binding efficiency, but the factor release is too fast. Relevant tests on the percentage of factors released into the solution within one month show that more than 30% of the factors escape into the solution by conventional means. The factors of the implants of conventional means are released in an unrestrained and explosive manner in the early stage, resulting in local high-level aggregation, which may not be conducive to healing to a certain extent and may even lead to tumor formation. Under the premise of ensuring personal safety, the factors of the implants should be induced to be in a safe fixed mode. Example 1 and Comparative Example 1 use titanium alloy with added strontium, which can achieve a safe fixed mode based on the percentage data of delayed release of factors.
[0045] Furthermore, the study showed that immobilized factors promote cell proliferation more than soluble factors. Soluble factors are degraded after being internalized, while immobilized factors can inhibit internalization, allowing them to promote proliferation for a longer period of time.
[0046] Furthermore, from the table, compared with other groups, the cell activity of the titanium alloy with added strontium using conventional physical adsorption methods is lower than that of other groups. This may be because strontium has a certain bactericidal ability and can kill some cells through protein cross-linking of cells; this method makes it unsuitable for clinical application. In contrast, the effect of titanium alloy-strontium element coated with erythritol liquid is significantly improved. Erythritol liquid can chelate with metals through its covalent bonds to form an adhesive film on the metal substrate, and it can remain in the human body for a long time. Slow release also helps tissues and implants to combine well.
[0047] In summary, the present invention adds a trace amount of rare earth element strontium to TC4, and while ensuring personal safety, forms a degradable organic strontium compound through the molecular release of the trace strontium element, which is released on the surface of the TC4 titanium alloy implant, promotes the attachment and growth of human tissue, improves the rapid repair of bone tissue, and increases the biological activity of bone integration; the titanium alloy-strontium element effect coated with erythritol liquid of the present invention is significantly improved, and the erythritol liquid can chelate with the metal through its covalent bond to form an adherent film on the metal substrate, and it can remain in the human body for a long time, and the slow release also helps the tissue and the implant to be well combined; the post-processing operation of the present invention is simple and low in price, and the action time of the degradable organic strontium compound that is continuously released in trace amounts is longer than the survival time of the growth factor, which is more conducive to improving the success rate of the operation.
[0048] The above-mentioned embodiment only expresses one implementation mode of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A medical implantable TC4 alloy, characterized in that: In terms of mass percentage, the TC4 titanium alloy includes: Al 5.5-6.75wt%, V 3.5-4.5wt%, Fe≤0.3wt%, C≤0.08wt%, O≤0.20wt%, N≤0.05wt%, H≤0.015wt%, Sr 0.02-0.08wt%, and the remainder Ti and unavoidable impurities.
2. A post-processing process of a medical implantable TC4 alloy product, characterized in that: Using the medical implantable TC4 alloy as claimed in claim 1, comprising the following steps: (1) adding raw materials according to the composition and proportion of the above-mentioned medical implantable TC4 alloy, the raw material alloy is smelted at least twice, and then subjected to ingot casting, drawing, shaping, and rounding processes to produce a master alloy rod; (2) The master alloy rod is loaded onto the EIGA device, and the master alloy rod is quickly melted to form powder; (3) screening the powder to obtain powder of a specified particle size, and printing the powder on the powder; (4) After the printing of the workpiece is completed, a stress removal heat treatment is performed, and a surface roughness treatment process is performed on the surface. After reaching the specified surface roughness, the workpiece is soaked in erythritol solution, and then subjected to conventional heat treatment. After the workpiece returns to room temperature, it is soaked in erythritol solution again to form a trace strontium compound on the surface that can continuously release a trace amount of alternative growth factors; (5) Subsequently, routine operations can be performed according to surgical requirements.
3. A post-processing process of a medical implantable TC4 alloy product as claimed in claim 2, characterized in that: In step (1), the first smelting of the at least two smeltings is carried out by a consumable electrode, a non-consumable electrode, an electron beam cooling hearth or a plasma arc cooling hearth furnace.
4. A post-processing process for a medical implantable TC4 alloy product as claimed in claim 2, characterized in that: In step (1), the second melting of the at least two meltings or the multiple meltings after the second melting are all vacuum melted in vacuum arc remelting, and alloy additives are not allowed to be added in the last vacuum melting.
5. The post-processing process of a medical implantable TC4 alloy product as claimed in claim 2, characterized in that: In step (3), the printing powder particle size D10 of the printed part is set to be above 18 microns, and the powder particle size D90 is set to be below 65 microns.
6. A post-processing process for a medical implantable TC4 alloy product as claimed in claim 2, characterized in that: In step (3), the print layer thickness of the printed part is 0.03-0.06 mm, the scanning interval is 0.12-0.18 mm, the scanning power is 280-300 W, and the main body scanning rate is 1300-1600 mm / s.